Spermatocyte cytokinesis requires rapid membrane addition mediated by ARF6 on central spindle recycling endosomes. - Dyer, N.; Rebollo, E.; Domínguez, P.; Elkhatib, N.; Chavrier, P.; Daviet, L.; González, C.; González-Gaitán, M. (Development, 2007)
The dramatic cell shape changes during cytokinesis require the interplay between microtubules and the actomyosin contractile ring, and addition of membrane to the plasma membrane. Numerous membrane-trafficking components localize to the central spindle during cytokinesis, but it is still unclear how this machinery is targeted there and how membrane trafficking is coordinated with cleavage furrow ingression. Here we use an arf6 null mutant to show that the endosomal GTPase ARF6 is required for cytokinesis in Drosophila spermatocytes. ARF6 is enriched on recycling endosomes at the central spindle, but it is required neither for central spindle nor actomyosin contractile ring assembly, nor for targeting of recycling endosomes to the central spindle. However, in arf6 mutants the cleavage furrow regresses because of a failure in rapid membrane addition to the plasma membrane. We propose that ARF6 promotes rapid recycling of endosomal membrane stores during cytokinesis, which is critical for rapid cleavage furrow ingression.